Effect Of Double Fuzzy Logic Controller (DFLC) Based On Power System Stabilizer (PSS) On A Tie- Line Two Generators System - Hasan, Hayfaa Mohammed Hussein; Sulaiman, Marizan; Omar, Rosli; Mohd Aras, Mohd Shahrieel (Asian Research Publishing Network (ARPN), 2017)
This research was proposed a new type of power system stabilizer based on fuzzy set theory, to improve the dynamic performance of a multi-machine power system. To have good damping characteristics over a wide range of operating conditions, speed deviation and it is derivative of a machine are chosen as the input signals to the fuzzy stabilizer on that particular machine. Fuzzy logic controller (FLC) Two area symmetrical systems connected via tie-line are measured to show via performance of these controllers. This research presents the analysis of change of speed (Δω), change of angle position (Δδ) and tie - line power flow (Δp). In tie-line system two generators control arrangement single fuzzy logic controller (SFLC) have been used as a primary controller, whereas double fuzzy logic controller (DFLC) used as a secondary controller. In addition to this, the system shows comparative between two controller single and double fuzzy controller has been used for the system to achieve the best results using Simulink/MATLAB. Double fuzzy controller has a greater effect on the tie-line system and become more smoothing than single fuzzy controller because has increased the damping of the speed Δω, angle rotor Δδ and power Δp.